2020
DOI: 10.3390/nu12113470
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Consumption Affects Glucocorticoid Signaling in the Liver of Young Female Rats

Abstract: The effects of early-life fructose consumption on hepatic signaling pathways and their relation to the development of metabolic disorders in later life are not fully understood. To investigate whether fructose overconsumption at a young age induces alterations in glucocorticoid signaling that might contribute to development of metabolic disturbances, we analysed glucocorticoid receptor hormone-binding parameters and expression of its target genes involved in gluconeogenesis (phosphoenolpyruvate carboxykinase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Studies have demonstrated that the administration of 10 % fructose in water for 3 weeks to healthy Wistar rats is associated with a state of oxidative stress due to an imbalance between production of ROS and antioxidant capacity (33,34). In addition, it is known that the incidence and progression of various health conditions, such as liver steatosis and other conditions, correlate with variations in oxidative stress and antioxidant defense enzyme levels (35).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that the administration of 10 % fructose in water for 3 weeks to healthy Wistar rats is associated with a state of oxidative stress due to an imbalance between production of ROS and antioxidant capacity (33,34). In addition, it is known that the incidence and progression of various health conditions, such as liver steatosis and other conditions, correlate with variations in oxidative stress and antioxidant defense enzyme levels (35).…”
Section: Discussionmentioning
confidence: 99%
“…For the measurement of xanthine oxidase activity, the adipose tissue was homogenized in 100 mMTris buffer (pH 7.4) containing protease inhibitors and sonicated (3 × 15 s at 10 MHz on ice) prior to 20 min centrifugation at 20,000 × g (4 °C). Hepatic cell extracts were prepared as described previously ( 56 ). Xanthine oxidase activity was measured spectrophotometrically on the Synergy H1 Hybrid Multi-Mode Reader (BioTek Instruments, Winooski, VT, United States) by estimating the rate of oxidation of xanthine to uric acid at 295 nm ( 57 ).…”
Section: Methodsmentioning
confidence: 99%
“…After consuming 60% fructose solution for 9 weeks, both male and female Wistar rats showed increased hepatic TNF alpha (TNFα), one of the markers of inflammation. 47 , 48 However, NFκB activation was only detected in male rats, which may be due to the protection effect of the enhanced glucocorticoid signaling restricted to female rats. 48 Intriguingly, consuming fructose under stressful conditions, as performed by Kovačević et al 49 in female Wistar rats, counteracted the effects of stress on hepatic lipid accumulation alone.…”
Section: Sweeteners and Nafldmentioning
confidence: 99%
“… 47 , 48 However, NFκB activation was only detected in male rats, which may be due to the protection effect of the enhanced glucocorticoid signaling restricted to female rats. 48 Intriguingly, consuming fructose under stressful conditions, as performed by Kovačević et al 49 in female Wistar rats, counteracted the effects of stress on hepatic lipid accumulation alone. Whether this is also a secondary effect of the elevated glucocorticoids remains unknown.…”
Section: Sweeteners and Nafldmentioning
confidence: 99%